PENGARUH EMPLOYEE STOCK OWNERSHIP PLAN (ESOP), PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR), INNOVATION, LEVERAGE, DAN FIRM SIZE TERHADAP CORPORATE FINANCIAL PERFORMANCE (Studi pada Perusahaan Manufaktur yang Listing di Bursa Efek Indonesia Periode 2013-2017) - Syahida, Asyifa Zuchruf; Prasetiono, Prasetiono (Faculty of Economics and Business Diponegoro University, 2019)
This study aims to test the influence of Employee Stock Ownership Plan, Corporate Social Responsibility disclosure, innovation, leverage, and firm size toward corporate financial performance. Corporate financial performance can be seen from the company’s profitability which measured by ROA. This research was conducted because there are differences in results from previous studies. The sample used in this study are manufacturing companies listed in Indonesia Stock Exchange during 2013-2017. This study used purposive sampling method with several criteria and outlier data removal to obtain a valid data, which remain as 230 observation data. Multiple regression analysis which is processed by SPSS 25 is used as an analysis technique consisting of classical assumption test and coefficient of determinant test, F statistical test, and t statistical test. The results of this research indicate that leverage has significant negative effect toward corporate financial performance and firm size has significant positive effect toward corporate financial performance. Meanwhile Employee Stock Ownership Plan has insignificant negative effect toward corporate financial performance. Corporate Social Responsibility disclosure and innovation has insignificant positive effect toward corporate financial performance which shows a unidirectional and insignificant relationship.